The expression pattern of circulating miR-590-3p as a promising diagnostic biomarker for early detection of epithelial ovarian cancer - Shawer, Heba (AUC Knowledge Fountain, 2015)
Epithelial ovarian cancer (EOC) is the most common type of ovarian tumors. The biomarkers, which are being used for EOC screening, have low sensitivity and specificity leading to late diagnosis and high mortality rate. Thus, identification of effective biomarkers for early diagnosis of ovarian cancer has become a high priority in research. Here we aim to address this problem by studying the expression of a potential molecular marker, miR-590-3p, in EOC. We examined the mRNA steady-state levels of various acknowledged biomarkers including cancer antigen-125 (CA125) which is being used for EOC screening, c-reactive protein (CRP) which expression was correlated with EOC stage and paired homeobox 2 gene (PAX2) whose expression is correlated with the histological grade to characterize the histo-pathological features of the specimens at the molecular level. We examined the expression of miR-590-3p in EOC patients’ serum and EOC tissues, using real-time PCR. The levels of circulating miR-590-3p showed to be significantly elevated in 84.6% of the EOC patients’ serum, with 76.92% sensitivity and 85.7% specificity at its optimal cutoff value. Tissue miR-590-3p showed to be upregulated in EOC tissues compared to normal ovarian tissues and highly correlated with high-grade poorly differentiated EOC. The adoption of the epithelial-mesenchymal transition biomarkers was enriched in EOC with high miR-590-3p levels. The potential downstream target genes, SOX2, LEF1 and PAX2, were predicted using miRanda and Targetscan in silco tools and their expression profiles were in silco examined using Oncomine data-mining platform and StarBase Pan-cancer analysis. We examined the levels of SOX2, LEF1 and PAX2 at the RNA and the protein levels via semi-quantitative PCR and western blot, respectively. Among the investigated potential target genes, only PAX2 showed negative correlation with the levels of miR-590-3p in EOC tissues, suggesting that miR-590-3p could acquire its role in EOC carcinogenesis through regulation of cellular differentiation in EOC.